A prospective study on the role of Octreotide in management of chyle fistula neck. (30th January 2015) - Jain, Avani; Singh, Shashank Nath; Singhal, Pawan; Sharma, Man Prakash; Grover, Mohnish
<x xml:space="preserve">Abstract</x> Objective To study the effectiveness of octreotide in managing chyle fistula neck and its effect on duration of hospitalization. Study Design Prospective study. Methods A total of 19 patients with chyle fistula following neck dissection over a period of 10 years were included in the study. All the patients first underwent conservative management of the chyle leak, including suction drainage, pressure dressings, bed rest, and nutritional modifications. In all of the cases, chyle leak persisted despite conservative management. Octreotide was started in a dose of 100 µg subcutaneously every 8 hours for 5 days in cases with low‐output leaks and for 7 days in cases with high‐output leaks. In all of the cases, the duration of chyle leak after starting treatment with octreotide and the duration of hospitalization was recorded. Results Chyle leak stopped in all the cases using octreotide. The mean duration of hospitalization was 13.8 days. Conclusion Chyle leak stopped within 5 days of starting octreotide in the low‐output cases and within 7 days in the high‐output cases. This permitted early resumption of a regular oral diet and reduced morbidity associated with chyle fistula. The rapid response and minimal side effect profile make octreotide a promising addition to the medical management of a chyle fistula. Level of Evidence 4. Laryngoscope, 125:1624–1627, 2015